Biases of professional exchange rate forecasts: Psychological explanations and an experimentally based comparison to novices - Johannes Leitner; Robert Schmidt; Peter Bofinger (University of Würzburg, Department of Economics, 2003)
The empirical performance of macroeconomic exchange rate models is more than disappointing. This dismal result is also reflected in the forecasting capabilities of professional analysts: all in all, analysts are not in a position to beat naïve random walk forecasts. The root for this deficient outcome stems from the fact that professional forecasts are to a large extend influenced by actual changes in exchange rates. A reasonable explanation for this behaviour can be taken from the behavioural finance literature. To test whether this characteristic tends to be general human behaviour in an uncertain environment, we analyse the forecasting behaviour of students experimentally, using a simulated currency series. Our results indicate that a topically oriented trend adjustment behaviour (TOTA) is a general characteristic of human forecasting behaviour. Additionally, we apply a simple model to explain professional and students forecasts.
Keywords: F31; F47; G12; G15; E27; D81; D7; C53; C92; 330; Foreign exchange market; forecasting; behavioural finance; anchoring heuristics; judgement; expertise; Wechselkurs; Prognose; Anlageverhalten; Verhaltensökonomik; Test